Hydrazone linked doxorubicin-PLA prodrug nanoparticles with high drug loading. (21st May 2018) - Gatti, Simone; Agostini, Azzurra; Palmiero, Umberto Capasso; Colombo, Claudio; Peviani, Marco; Biffi, Alessandra; Moscatelli, Davide
Abstract: An optimal drug delivery system should be characterized by biocompatibility, biodegradability, high drug loading and favorable drug release profile. To achieve this goal a hydrazone linked doxorubicin-poly(lactic acid) prodrug (PLA-DOX) was synthesized by the functionalization of a short polymer chain produced by ring opening polymerization. The hydrophobic prodrug generated in this way was nanoprecipitated using a block copolymer to form polymeric nanoparticles (NPs) with a quantitative loading efficiency and a high and tunable drug loading. The effects of the concentration of the PLA-DOX prodrug and surfactant were studied by dynamic light scattering showing a range of NP size between 50 and 90 nm and monodispersed size distributions with polydispersity indexes lower then 0.27 up to a maximum DOX concentration of 27% w/w. The release profile of DOX from these NPs, tested at different pH conditions, showed a higher release rate in acidic conditions, consistent with the nature of the hydrazone bond which was used to conjugate the drug to the polymer. In vitro cytotoxicity studies performed on BV2 microglia-like cell line highlighted a specific cytotoxic effect of these NPs suggesting the maintenance of the drug efficacy and a modified release profile upon encapsulation of DOX in the NPs.